Advances in Nitrogen-Rich Wastewater Treatment: A Comprehensive Review of Modern Technologies - Abdullah Omar (6468326) (2024)
Nitrogen-rich wastewater is a major environmental issue that requires proper treatment before disposal. This comprehensive overview covers biological, physical, and chemical nitrogen removal methods. Simultaneous nitrification–denitrification (SND) is most effective in saline water when utilizing both aerobic and anoxic conditions with diverse microbial populations for nitrogen removal. Coupling anammox with denitrification could increase removal rates and reduce energy demand. Suspended growth bioreactors effectively treated diverse COD/N ratios and demonstrated resilience to low C/N ratios. Moving biofilm bioreactors exhibit reduced mortality rates, enhanced sludge–liquid separation, increased treatment efficiency, and stronger biological structures. SND studies show ≥90% total nitrogen removal efficiency (%RETN) in diverse setups, with Defluviicoccus, Nitrosomonas, and Nitrospira as the main microbial communities, while anammox–denitrification achieved a %RETN of 77%. Systems using polyvinyl alcohol/sodium alginate as a growth medium showed a %RETN ≥ 75%. Air-lift reflux configurations exhibited high %RETN and %RENH4, reducing costs and minimizing sludge formation. Microwave pretreatment and high-frequency electric fields could be used to improve the %RENH4. Adsorption/ion exchange, membrane distillation, ultrafiltration, and nanofiltration exhibit promise in industrial wastewater treatment. AOPs and sulfate-based oxidants effectively eliminate nitrogen compounds from industrial wastewater. Tailoring proposed treatments for cost-effective nitrogen removal, optimizing microbial interactions, and analyzing the techno-economics of emerging technologies are crucial. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su16052112